STUDYING THE LEVEL OF SOCIAL WORKERS AWARENESS OF THE CONNECTION BETWEEN SOCIAL WORK FOR PEOPLE WITH DISABILITIES AND THE CONDITIONS OF THE COVID-19 PANDEMIC - Mariana Zhelyazkova (Science & Research)

(untitled)
For a period of about three years (from the beginning of 2020 till the beginning of May 2023, when the WHO canceled the status of pandemic), the COVID-19 pandemic was active in the Republic of Bulgaria. The pandemic had an impact on all spheres of life, including social work for persons with disabilities in our country. The topic of this study is the level of social workers’ awareness of the connection between social work for persons with disabilities and the conditions of the COVID–19 pandemics. Some aspects of awareness in the centers, working with disabled people, have been studied. Purpose of the study: To study some aspects of the level of social workers awareness on the connection betwen social work for people with disabilities and the conditions of the COVID-19 pandemic. Scope and methods: A survey was conducted among 40 social workers in 5 centers working with persons with disabilities from the city of Sliven regarding their activities under the conditions of the COVID-19 pandemic. Statistical processing of the research results was completed. Results and discussion: Social workers want to be informed to a different degree about various topics related to the COVID–19 pandemic. Most of them (37.5%) would like to have information about work-specific activities under pandemic conditions. For 30% of the social workers it is important to understand what the symptoms of the disease are. Apparently, that same number of social workers (30%) need to know how to react in certain situations of the pandemic. Only a small part of the respondents (7.5%) need practice in a pandemic environment. Unfortunately, about 30% of all social workers refuse to have any information related to the impact of COVID–19 on their work. The total of the answers to this question is greater than 100% since social workers gave more than one answer.